Experiências de mulheres com câncer de mama no manejo da fadiga secundária à quimioterapia - Cunha, Nayara Ferreira (2017)
Introduction: Among the adverse reactions due to chemotherapy, the fatigue has had several impacts in quality of life of cancer patients. The absence of reporting the fatigue as an adverse reaction by patients undergoing chemotherapy, the non-appreciation of the complaint by the health professionals and the difficulty of handling this adverse reaction, has made the search for complementary practices/ non-pharmacological strategies for the relief of secondary fatigue due to chemotherapy an alternative for those patients. Objective: The aim of the study was understanding the experiences of women with breast cancer in chemotherapy with the use of complementary practices/ non-pharmacological strategies for fatigue management is the aim of this study. Methods: It is explicative study, with qualitative approach, theoretical reference of medical anthropology and developed with four women. Data collection was conducted with semi-structured interviews, audio records and observation. For the organization and analysis of the data the thematic analysis was used. Results: Secondary fatigue due to chemotherapy generated discomfort and limitations to the breast cancer women on chemotherapy participants. To deal with this adverse reaction different complementary practices/non-pharmacological strategies were identified: rest; energy conservation; food care; practice of religious activities; walking and body movement; plant care; family, informal and professional support, which were implemented through self-care and care received and provided momentary relief or relaxation. We understand that the sense attributed to the experiences of fatigue was the limitation to daily routine, that hold back women in fulfilling their roles. Regarding complementary practices/nonpharmacological strategies used for the management of fatigue, we perceive that the sense attributed was the possibility of feeling capable and reaching relief, even if momentary, allowing us to feel better, confident and able to continue until the treatment. Conclusion: The study demonstrated the importance of understanding the experiences of fatigue and the need to use the complementary practices/nonpharmacological strategies by women with breast cancer, giving voice to their discourses, knowledge, beliefs and cultural values. The health team should associate cultural understanding with scientific knowledge in its care practices, in addition to developing and improving complementary practices/ non-pharmacological strategies aimed at integral care.